2017
DOI: 10.1097/ana.0000000000000407
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Management of Adult Patients With External Ventricular and Lumbar Drains: Guidelines From the Society for Neuroscience in Anesthesiology and Critical Care

Abstract: External ventricular drains and lumbar drains are commonly used to divert cerebrospinal fluid and to measure cerebrospinal fluid pressure. Although commonly encountered in the perioperative setting and critical for the care of neurosurgical patients, there are no guidelines regarding their management in the perioperative period. To address this gap in the literature, The Society for Neuroscience in Anesthesiology & Critical Care tasked an expert group to generate evidence-based guidelines. The document generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 197 publications
(231 reference statements)
0
25
0
Order By: Relevance
“…The Society for Neuroscience in Anesthesiology and Critical Care has published guidelines for the perioperative management of patients with external ventricular drains and lumbar drains. 58 The readers should familiarize themselves with these guidelines (https://www.snacc.org/wp-content/uploads/2017/03/ Review Article MARCH_27_2017_EVD_LD_SNACC_Education_ Document.pdf; accessed August 11, 2020).…”
Section: Rapid Restoration Of Cerebral Perfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Society for Neuroscience in Anesthesiology and Critical Care has published guidelines for the perioperative management of patients with external ventricular drains and lumbar drains. 58 The readers should familiarize themselves with these guidelines (https://www.snacc.org/wp-content/uploads/2017/03/ Review Article MARCH_27_2017_EVD_LD_SNACC_Education_ Document.pdf; accessed August 11, 2020).…”
Section: Rapid Restoration Of Cerebral Perfusionmentioning
confidence: 99%
“…The external ventricular drain should be used to monitor ICP and CPP. It should be referenced at the level of external auditory meatus 58 and typically left open to drain CSF if the ICP exceeds 20 mmHg. Jugular venous oximetry can detect intraoperative cerebral oxygen desaturation 131 and guide anesthetic interventions such as hyperventilation therapy and management of perfusion pressure, fluids, and oxygenation to optimize the cerebral physiology.…”
Section: Intraoperative Monitoringmentioning
confidence: 99%
“…TGF-ÎČ3 is a cytokine that is involved in embryogenesis, cell differentiation and wound healing 24 . A study found that TGF-ÎČ genes, including TGF-ÎČ3, were associated with the risk of metabolic syndrome among Taiwanese individuals 25 . The neuronal RAP1A gene was downregulated in both permissive and standard feeding group on heatmap, although downregulation in the permissive underfeeding was more profound, but the differential expression was not statistically significant on individual patient data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The method and frequency of CSF sampling, as well as the clinical symptoms that may be confounded by the primary and secondary neurological insults, also adds to the challenge [114,116]. On the other hand, there are recommendations against extended prophylaxis [119]. First, increased risk of Clostridium difficile diarrhoea and the development of antibiotic-resistant organisms have been documented [119].…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, there are recommendations against extended prophylaxis [119]. First, increased risk of Clostridium difficile diarrhoea and the development of antibiotic-resistant organisms have been documented [119]. Second, there are concerns over a microbiological spectrum shift from gram-positive to more noxious gram-negative micro-organisms due to colony selection pressure [95,117,120].…”
Section: Literature Reviewmentioning
confidence: 99%